The black coloring in the novel “The remained. Black raven” by Vasyl Shkliar (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
The article examines the semantics, symbolic meaning, author’s using of colourative  black in Basyl Shklyar’s novel “Zalyshenets. Chornyi Voron”. The ways of realization of colourative contrast are outlined.
Keywords: colourative; colour symbol; symbolic meaning; attributive component